Syringocystadenoma Papilliferum (Northern International Medical College Journal, 2015)
Syringocystadenoma Papilliferum (SCAP) is a rare papilloma resembles to benign tumour. It is characterized by extensive papillary epithelial elements growing in to dermis. A 9 years old boy presented with slowly growing dome shaped plaque consists of clusters of rose-red like vesicles of firm consistent, smooth-surfaced papules over the occipital region of the scalp. There was no family history of such type of lesions. Histopathological examination showed few cystic invaginations from the epidermis into dermis. Papillary projections are extending from the base of the cyst into lumen of the cystic spaces that consistent with Syringocystadenoma Papilliferum (SCAP).The treatment of choice is surgical excision.Northern International Medical College Journal Vol.5(2) 2014: 349-350